Vaccine uptake and COVID-19 frequency in pregnant syrian immigrant women - Sezerol, Mehmet Akif; Altaş, Zeynep Meva (MDPI, 2023)
Immigrants have difficulties in the use of essential health services such as vaccinations. Vaccine uptake among pregnant immigrant women is very low. The aim of the study was to examine the vaccination status of pregnant immigrant women who received health services in an immigrant health center (IHC) affiliated to primary health care institutions. The research is a retrospective-designed cross-sectional type of study. The study sample consists of pregnant Syrian women who received health care from the strengthened IHC of a District Health Directorate in Istanbul between August 2020 and 2022. Age, trimesters, number of pregnancies, high-risk pregnancy status, vaccination dates and status against influenza, COVID-19 and tetanus, and vaccine types of COVID-19 were evaluated. The statistical significance level was determined as p < 0.05. None of the pregnant women had received the influenza vaccine. Of the women whose tetanus vaccine data were evaluated, 29.7% had received at least two doses of the tetanus vaccine. Of the pregnant women, 19.4% were vaccinated against COVID-19 with a minimum two doses and 4.2% had a COVID-19 infection during their pregnancy. None of the women with the COVID-19 infection were fully vaccinated against COVID-19. The vaccine uptake of pregnant immigrant women is very low. Public health interventions are needed to improve vaccination coverage among disadvantaged groups.
Keywords: Immigrants; Vaccination; Pregnant Women; COVID-19